Evaluation of alteration in oral microbial flora pre- and postradiation therapy in patients with head and neck cancer - Ayanambakkam Hemasundar Harini Priya; Rajmohan; Hari Priya Arun Kumar; Shakthi Akash Raj; Sai Archana; Bharathwaj Venkatanarasu (Wolters Kluwer Medknow Publications, 2020)
Introduction: For decades now, head and neck cancer (HNC) remains to be one of the deadliest; per se the treatment for the same has been evolving for the past years. Radiation therapy (RT) has been one among the various treatment modalities adopted to treat HNC. The fact that RT can affect the quality of life in these patients cannot be denied. In patients with HNC, these can bring about a wide array of lesions in oral cavity and its associated structures as these areas are invariably affected due to exposure to radiation as such. These include alteration in salivary parameters, changes in microbial flora, and occurrence of radiation caries. Aim: In our study we aimed at assessing the alteration in oral microbial flora inclusive of Streptococcus mutans and Lactobacillus colony count before and after RT. Materials and Methods: Saliva and plaque samples were collected from patients with HNC, who were prescribed to undergo intensity-modulated radiation therapy (IMRT) amounting to a mean radiation dosage of 60 Gy units. The aforementioned samples were collected at three different intervals, before, immediately after, and 6 months after RT. The samples were cultured in selective media in three different dilutions (1:10, 1:100, and 1:1000). Following with colony counting is carried out using a standardized colony counter. Conclusion: The results showed a significant alteration in microbial flora pre- and post-RT. Individual parameters do not show a single stand in causing these changes. Moreover, these changes seem to have earned a multifactorial contribution.